Fertility in Rostock and Rural Mecklenburg-Schwerin in the 19th Century - Siegfried Gruber; Rembrandt Scholz (Historical Life Course Studies)
In this paper we first set out to evaluate how much the fertility between Rostock as an urban settlement differed from the surrounding rural area of Mecklenburg-Schwerin, in the 19th century. The available microdata allows for a more in-depth analysis compared to previous research based on aggregate data. The censuses of 1819, 1867, and 1900 provide data for using the Own-Children-Method. We analyse the urban-rural difference, the influence of occupational groups in the city of Rostock and its rural surroundings, and finally the influence of migration on fertility in the city of Rostock. Immigration from rural areas and other cities was the main reason for the population increase of Rostock in the 19th century and this could have affected its fertility levels. Overall fertility was higher for rural areas than for urban ones, while marital fertility was more or less the same. Marital fertility was almost the same for all occupational groups, even for the agricultural sector. Migration had no visible effect on marital fertility, which is both interesting and unexpected. The most important factor for the level of overall fertility was the proportion of married people, which was an outcome of the possibilities offered by different economic sectors and environments.